Vivências e estágios na realidade do Sistema Único de Saúde: influências na formação e atuação dos enfermeiros - Fettermann, Fernanda Almeida (2015)
In the area of health various activities are carried out with the objective of training completion, among them stands out the Experience Project Stage and Reality of the Unified Health System (VER-SUS). This project provides students with a multidisciplinary practice health work in which several graduate courses in an integrated way, know and reflect on the Health System and its management processes, teaching, social control and service. Thus, the guiding issue of this research was: What influences were generated in the training and professional performance of nurses who experienced VER-SUS? It aimed to identify the influences of Experiences and Internships Reality of the Unified Health System, training and nurses performance mode. Specific objectives: to know the contributions of VER-SUS in the insertion of extracurricular activities for training students of nursing program; know the influences that VER-SUS provided an opportunity for the social teaching-service-management-control integration in the health field; describe how teamwork during the experience of VER-SUS. Qualitative research, exploratory and descriptive performed with 14 nurses who performed during his graduation, VER-SUS-RS, in 2012. Data collection took place between October 2014 and January 2015, after approval the research project of the Protocol by the Ethics Committee on Human Research, through semi-structured interview. Data were analyzed, discussed and interpreted following the Bardin Content Analysis. . The ethical aspects of research were respected, according to Resolution No. 466 / 2012do National Health Council The content analysis three categories emerged: VER-SUS influences the formation and performance in nursing; interprofessional education: a path to shared learning and integration between teaching, services, management and social control: a challenge to VER-SUS. The results showed that a dichotomy between the guidelines of the Curriculum Guidelines The VER-SUS made possible the creation of emotional ties, joint moments and exchange of experience in the multidisciplinary team and provided an opportunity to understand how the system management develops and implements policies, practices in services and the role of social control in the search and struggle for their rights, however, it is understood that these segments are seen to disconnect form. It concludes that the VER-SUS experience reflected in the professional practice of nurses in order to look for horizontal subjects.